Can we reduce the symptoms of chronic fatigue syndrome by regulating micronutrients? A review - AKDUMAN, GÜL (My University, 2023)
Introduction: Deficiencies of some micronutrients have been observed in chronic fatigue syndrome patients, but the underlying cause has not been fully understood. The aim of this study was to investigate whether there is a relationship between CFS and micronutrients. Methods: Related articles searched the combinations of the following terms which were used for the search in the Web of Science database: \"Chronic Fatigue Syndrome\" OR \"Chronic FatigueFibromyalgia Syndrome\" OR \"Postviral Fatigue Syndrome\" AND \"vitamins\" OR \"minerals\" OR \"micronutrients\". Articles that met the inclusion criteria were included. Results: The initial search resulted in 225 studies, with 11 studies fully meeting the inclusion criteria. In these studies, it has been shown that micronutrients may play a role in the etiology of CFS, and that supplemented micronutrients can positively affect the symptoms of CFS. Conclusion: Although there seems to be a close relationship between CFS-related syndromes and nutritional status, the literature on this subject remains limited. The results of the studies were not compatible with each other due to differences in the studies. Therefore, new studies are needed to fully explain the relationship between CFS and micronutrients.
Keywords: Beslenme ve Dietetik; Sosyal ve Beşeri Bilimler; Sosyoloji; Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Sağlık Bilimleri; Mühendislik ve Teknoloji; Nutrition and Dietetics; Social Sciences and Humanities; Sociology; Agricultural Sciences; Agriculture; Food Engineering; Health Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Sosyal Bilimler (SOC); Tarım Bilimleri; Sosyal Bilimler Genel; BESLENME VE DİYETETİK; GIDA BİLİMİ VE TEKNOLOJİSİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Agriculture & Environment Sciences (AGE); Social Sciences (SOC); AGRICULTURAL SCIENCES; SOCIAL SCIENCES, GENERAL; NUTRITION & DIETETICS; FOOD SCIENCE & TECHNOLOGY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Yemek bilimi; Yaşam Bilimleri; Beslenme ve Diyetetik; Halk, Çevre ve İş Sağlığı; Food Science; Life Sciences; Public Health, Environmental and Occupational Health; autonomic dysfunction; Chronic fatigue syndrome; cognitive impairment; micronutrients; minerals; vitamins